Sexual attraction in therapy : clinical perspectives on moving beyond the taboo : a guide for training and practice - Luca, Maria, 1956- (Chichester, West Sussex ; Malden, MA : Wiley Blackwell, 2014)
Sexual Attraction in Therapy presents new findings from multiple perspectives into the complex phenomenon of sexual attraction in therapy. Detailed clinical examples and strategies from expert contributors demonstrate how therapists can engage with sexual attraction, when it arises, in positive ways that facilitate client progress and ensure appropriate professional conduct. Challenges practitioners to think about sexual attraction as a normal dynamic developing through the unique intimacy of the therapy encounterPresents new findings from research to enrich unde.
Committing to Values-Congruent ActionThe Importance of Words and Thoughts in ACT; Sexual Fantasy and ACT; The ACT Model of Psychopathology; Lack of clarity of values; Attachment to the conceptualized self; Cognitive fusion; Dominance of outmoded scripts; Experiential avoidance; Inaction, impulsivity or rigidity; Getting Unstuck; Mindfulness; Defining valued directions; Acceptance training; Commitment (taking action); Cognitive defusion and self as context; Clinical Strategy for Managing Sexual Attraction; The white board; References; 7: Addressing Sexual Attraction in Supervision.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Psychotherapy -- Practice; Clinical psychologists -- Training of; Psychotherapists -- Sexual behavior; Psychotherapist and patient; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Clinical psychologists -- Training of; Psychotherapist and patient; Psychotherapists -- Sexual behavior; Psychotherapy -- Practice; Clinical psychologists -- Training of; Psychotherapist and patient; Psychotherapists -- Sexual behavior; Psychotherapy -- Practice; Electronic books; Electronic books